2003
DOI: 10.1007/s11664-003-0094-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of deep levels on the photocurrent transients in semi-insulating GaAs

Abstract: The photocurrent transients, I PC (t), were studied in semi-insulating (SI) GaAs during a low-temperature (low-T) illumination. Unusual transients were explained by the model, relating I PC (t) to the deep levels/traps and their occupancy. Such traps were actually detected and characterized by the independent measurements of the thermally stimulated currents (TSCs). The processes of the generation, recombination, and capture were described by a set of coupled differential equations and solved numerically. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It can be seen in Figure 1c that the initial macroscopic transient delay to constant photocurrent density I takes several tens of seconds (time t ) after the laser is switched on under ‐ V . In fact, the time scale of the transient delay is closely related to the structures of the different materials, for example poly(phenylene vinylene) (microseconds),27 pentacene (several tens of seconds)28 and semi‐insulator GaAs at low temperature (a few hundreds of seconds) 29. This is thought to be mainly due to the impact of deep‐level trapping on the free‐carriers.…”
Section: Methodsmentioning
confidence: 99%
“…It can be seen in Figure 1c that the initial macroscopic transient delay to constant photocurrent density I takes several tens of seconds (time t ) after the laser is switched on under ‐ V . In fact, the time scale of the transient delay is closely related to the structures of the different materials, for example poly(phenylene vinylene) (microseconds),27 pentacene (several tens of seconds)28 and semi‐insulator GaAs at low temperature (a few hundreds of seconds) 29. This is thought to be mainly due to the impact of deep‐level trapping on the free‐carriers.…”
Section: Methodsmentioning
confidence: 99%
“…So the system starts at and relaxes back into thermal equilibrium for every given temperature. In contrast to low temperature studies of GaAs [11,13] (e.g. simulations of the EL2 photoquenching effect), where equilibrium occupations of the bands are practically zero and can be neglected, they are important for the simulation of negative peaks for temperatures above 300 K, where transients are known to show a drop below equilibrium values [6].…”
Section: The Rate Equation Systemmentioning
confidence: 99%
“…the Fermi level in the samples). The model assumes an additional recombination center (RC), which has been suggested several times [9][10][11]. It will be shown that such a center is an important precondition for the formation of negative EL2 peaks.…”
Section: Introductionmentioning
confidence: 99%